Modulation of Endothelial Cells Fibrinolytic Activity by Platelets - Menashi, S; He, L; Soria, C; Soria, J; Thomaidis, A; Legrand, Y (Thrombosis and Haemostasis, 1991)
Interaction between endothelial cells (EC) and platelets in culture was shown to regulate the fibrinolytic system of the aortic EC. Untreated porcine EC from aorta exhibited almost no net fibrinolytic activity and zymographic assay have shown a single fibrin lysis band of 105 kDa corresponding to a tPA-PAI complex. Incubation of aortic EC with intact platelets stimulated a cell-associated fibrinolytic activity of the urokinase type as evidenced by a plasminogen-dependent fibrin independent amidolytic activity, and the appearance of a new 48 kDa lysis band on zymography. However, in the culture medium of platelet-treated aortic EC, a new lysis band of. 92 kDa appeared with no associated amidolytic activity suggesting that the 48 kDa plasminogen activator secreted by the aortic EC after treatment with platelets is complexed to the inhibitor PAI1. This modulation of fibrinolytic activity depends on the EC origin sin0e it is not observed with pulmonary artery EC, and represents a new concept in fibrinolysis regulation by cell-cell interaction.